2012
DOI: 10.1039/c1cc15210f
|View full text |Cite
|
Sign up to set email alerts
|

Direct amide formation from unactivated carboxylic acids and amines

Abstract: The direct coupling of unactivated carboxylic acids with amines can be performed in toluene 110 °C in the absence of catalyst. The use of simple zirconium catalysts at 5 mol% loading gave amide formation in as little as 4 h.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
174
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 309 publications
(178 citation statements)
references
References 28 publications
2
174
0
2
Order By: Relevance
“…11 Recently, it was shown that a significant amount of the 15 amide product can be formed even at lower temperatures, usually with azeotropic removal of water. 12,13,14 The yields of the thermal amidation reaction is highly substrate dependent, as well as dependent on temperature, substrate concentration, solvent and other reaction parameters. As an example, the thermal yield of N-20 (4-methylbenzyl)-3-phenylpropanamide at 110 ºC under neat conditions was reported to be 58%, whereas the same product was formed quantitatively in toluene at 2 M concentration with the same reaction time and temperature (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…11 Recently, it was shown that a significant amount of the 15 amide product can be formed even at lower temperatures, usually with azeotropic removal of water. 12,13,14 The yields of the thermal amidation reaction is highly substrate dependent, as well as dependent on temperature, substrate concentration, solvent and other reaction parameters. As an example, the thermal yield of N-20 (4-methylbenzyl)-3-phenylpropanamide at 110 ºC under neat conditions was reported to be 58%, whereas the same product was formed quantitatively in toluene at 2 M concentration with the same reaction time and temperature (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%
“…As an example, the thermal yield of N-20 (4-methylbenzyl)-3-phenylpropanamide at 110 ºC under neat conditions was reported to be 58%, whereas the same product was formed quantitatively in toluene at 2 M concentration with the same reaction time and temperature (Scheme 1). 13 For comparison, the structurally similar N-benzylphenylacetamide 25 was formed in only 13% yield or less, when phenylacetic acid and benzylamine were allowed to react in THF at 70 ºC at a concentration of 0.4 M and a reaction time of 24 hours. 15 The literature on thermal amidation is not covered in this review unless the non-catalysed reaction is specifically mentioned by the 30 authors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These derivatives were associated with broad spectrum of biological activities including antituberculosis, 25 …”
Section: 23mentioning
confidence: 99%
“…A novel amide-bond forming method recently published by Allen et al was adopted to form the desired amides without the requirement for extensive purification. [193] The acid and the amine were refluxed in toluene overnight with a ZrCp 2 Cl 2 Lewis acid catalyst to yield, in most cases, the desired amide as the only product in 100 % conversion.…”
Section: Scheme 25mentioning
confidence: 99%